Kajian Konseptual Ruang Lingkup Kurikulum Pendidikan Agama Islam - Mardiah Astuti; Nabela Veronika; Asharil Fajri; Rahma Septa Ramadhan; Yoka Rajabna; Merlin Agustin; Annisa Az-Zahra; Al Zahra (Educational Journal, 2025)
This study aims to conceptually examine the scope of the Islamic Religious Education (PAI) curriculum as the foundation for shaping students’ faith, morals, and character. The research employs a qualitative approach with a library research method by analyzing various literature sources related to curriculum theory and Islamic education. Data were analyzed using content analysis to explore the main components within the scope of the PAI curriculum. The findings indicate that the scope of the PAI curriculum includes the Qur’an and Hadith, Aqidah Akhlak, Fiqh, Islamic Cultural History, and Arabic Language. These components function integrally to develop students’ cognitive, affective, and psychomotor aspects in a balanced way. The PAI curriculum continues to evolve in response to educational needs and societal changes, culminating in the Merdeka Curriculum, which emphasizes character formation and the strengthening of the Pancasila Student Profile. In the modern era, the PAI curriculum serves as a moral safeguard and a means of character education, preparing students to face global challenges while maintaining their Islamic and national identity.